Diskursus Tafsir bi al-Ma’tsur - Muhamad Yoga Firdaus; Nida Husna Abdul Malik; Hanna Salsabila; Eni Zulaiha; Badruzzaman M Yunus (Jurnal Dirosah Islamiyah, 2023)
This research explores Tafsir bi al-Ma'tsur, or Qur'an interpretation via history. This qualitative research method uses literature and historical interpretation. This paper discusses the history of Tafsir bi al-Ma'tsur, its restrictions, and scholarly disagreements over it. This study finds that Tafsir bi al-Ma'tsur is an interpretation based on Qur'anic verses, the Prophet Muhammad's viewpoints, companions, and scholars, commencing with the interpretation of Qur'anic verses with Qur'anic verses. 'an, the Qur'an's hadith, the Companions' atsar, and the Tabi'in's view. The Qur'an must be interpreted using a manner agreed upon by scholars to be in compliance with Shari'a. If the interpretation is done honestly and according to the manner approved by the commentators, it will obtain two rewards from Allah SWT if it's accurate, but only one if it's wrong, according to the Prophet SAW's statements on Ijtihad. This research should aid Qur'an scholars and interpreters. This research explains Tafsir bi al-Ma'tsur-related issues. This research offers a complete review of all western scientists' perspectives of Qur'anic exegesis literature to update our knowledge of Tafsir bi al-Ma'tsur.